PENERAPAN METODE ROLE PLAYING (BERMAIN PERAN)UNTUKMENGURANGI KESALAHANSISWA DALAM MENYELESAIKAN SOALPADA MATERIARITMETIKASOSIAL KELAS VIIA SMPN 1 SUKOWONOSEMESTER GANJIL TAHUN AJARAN 2012/2013 - Sha’adhah, Ziadatus; Hobri, H; Setiawan, Toto' Bara (Department of Mathematics Education , University of Jember, 2013)
Abstract.The aim of the study is to describe the implementation of role playing which decrease the student's error, to describe the student's activities in implementation of role playing method and to describe reduction of the student's error in completing questions after the implementation of role playing method. The subject of the study is the students of VII A class at SMPN Sukowono. In addition, the research design that is used in this study is classroom action research. The data were collected by using observation, interview, achievement test and documentation. The percentage result of the student’s activity observation showed that 54.91% in the beginning learning activity and 71.23% in the end of student’s learning activity. Moreover, the percentage of teacher’s activity is 90% and 96.67%. Besides that, the percentage of the student’s error in completing questions showed that it decreased from 42, 43% to 29.14%. Based on the result of the research, it can be concluded that the implementation of role playing method goes well, so it can help to decrease the student’s error in completing question of social arithmetic. Key Words : Role Playing, student’s error,sosial arithmetic.